2018
DOI: 10.3126/jbssr.v2i1-2.20957
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Merger Effect on Financial Performance of Banking and Financial Institutions in Nepal

Abstract: <p>Merger and Acquisition is relatively new reorganization practice undertaken to strengthen the BFIs in the Nepalese financial market. This study makes an attempt to analyze the financial performance of merged banking and financial institutions relative to their pre-merger performance, and assess the perception of the stakeholders towards merger. Six banks and financial institutions are considered as sample to undertake this study along with 120 respondents for secondary and primary data respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
1
8
2
1
Order By: Relevance
“…This study found that the loan quality significantly deteriorates after merger in most of the cases and profitability measured in terms of ROA and ROE was adversely affected in most of the cases after the merger. Therefore, it has suggested that the merger should not be considered as the definite solutions to overcome the challenges faced in the market enough evaluation is needed to select the right partners before executing the merger (Shrestha, Thapa, & Phuyal, 2017). The finding was slightly differed with the finding of present study because the present study had shown the significant improvement in the ROA and ROE in post-merger phase.…”
Section: Financial Performance Of Bfis After Mergercontrasting
confidence: 81%
See 2 more Smart Citations
“…This study found that the loan quality significantly deteriorates after merger in most of the cases and profitability measured in terms of ROA and ROE was adversely affected in most of the cases after the merger. Therefore, it has suggested that the merger should not be considered as the definite solutions to overcome the challenges faced in the market enough evaluation is needed to select the right partners before executing the merger (Shrestha, Thapa, & Phuyal, 2017). The finding was slightly differed with the finding of present study because the present study had shown the significant improvement in the ROA and ROE in post-merger phase.…”
Section: Financial Performance Of Bfis After Mergercontrasting
confidence: 81%
“…In contrast to the above findings was reported in the study of Shrestha, Thapa, & Phuyal (2017). A Comparative Study of Merger Effect on Financial Performance of Banking and Financial Institutions in Nepal makes an attempt to analyze the financial performance of merged banking and financial institutions relative to their pre-merger performance, and assess the perception of the stakeholders towards merger.…”
Section: Financial Performance Of Bfis After Mergermentioning
confidence: 78%
See 1 more Smart Citation
“…Studies in the Nepali context by Sharma (2018) and Acharya (2020) found a positive impact of mergers on the performance of financial institutions while the studies by Dwa and Shah (2017) and Chhetri and Baral (2018) found no such effect. On the other hand, in contrast to mergers between smaller financial institutions, positive effects of mergers are found if bigger and stable parties including commercial banks are bidders (Shrestha, et al, 2017).…”
Section: Review Of Empirical Studiesmentioning
confidence: 88%
“…There are ample evidences for a comprehensive account of banks mergers in developed countries and a few of the emerging ones, but less of Nepal (Acharya, 2020; Chhetri & Baral, 2018;Dwa & Shah, 2017;Gurung, 2013;Pathak, 2013;Sharma, 2018;Shrestha, et al, 2017), signifying the requirement for further research in the Nepali context.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%